Application of the Concept of Asset and Liability Management (ALMA) in the Islamic Banking System - Choirunnisak Choirunnisak (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2022)
This study discusses the application of the concept of asset and liability management (ALMA) in the banking system. The method used in this research is library research with a qualitative approach, where the data are obtained from books, journals, articles and the like that discuss the theme. After that, it was validated, and analyzed descriptively. The results of this study are: Application of Asset and Liability Management in banking institutions, both Islamic banks and conventional banks must go through an assessment of the budget, make income plans, evaluate investment performance in the past, unify the distribution of bank assets and liabilities and implement asset and financial strategies obligation